(untitled) (Nexo Revista Científica, 2021)
The article examines the content of public debt policy as an object of economic security in terms of methodological and practical aspects based on the assessment of debt sustainability using a system of indicators. The authors raise the issue of the need to develop a public debt management mechanism, to search for new strategies and tools, including by strengthening the functional role of international financial institutions.